Characterization of extracellular polymeric substances from Synechocystis sp. PCC6803 under Cd (II), Pb (II) and Cr (VI) stress. Issue 4 (August 2021) - Cui, Linlin; Fan, Ling; Li, Zhanfei; Wang, Junjun; Chen, Ran; Zhang, Yejuan; Cheng, Jinju; Wu, Xueling; Li, Jiaokun; Yin, Huaqun; Zeng, Weiming; Shen, Li
Abstract: Research regarding interactions between heavy metal ions and cyanobacteria is significant for the industrial application of cyanobacteria in wastewater treatment. The effects of Cd (II), Pb (II) and Cr (VI) on Synechocystis sp. PCC6803 extracellular polymeric substances (EPS) was investigated. In the absence of the EPS on cell surface, the adsorption amount of cyanobacterial cells to heavy metal ions reduced. Lots of metal ions precipitation on cyanobacterial cells surface were observed by SEM-EDX. The increase of exopolysaccharide contents was more obvious than extracellular protein contents under the heavy metal ions following metal ion exposure. The amide I was most sensitive to metal ion stimulation in functional group of extracellular proteins, but the interaction of metal ions with polysaccharides occurred prior to that with proteins. These results comprehensive proved that the EPS have significant impacts on cyanobacteria, thereby affecting the combination with heavy metals. Such insights will benefit our knowledge of the interactions between heavy metal ions and cyanobacterial EPS and provided theoretical guidance on the application of heavy metal sewage treatment by cyanobacteria. Graphical Abstract: ga1 Highlights: The higher the concentration of Cd(II), Pb(II), and Cr(VI), the stronger the inhibition to the growth of Synechocystis sp. PCC6803, and Cd(II) was the most toxic compound. The presence of heavy metal ions would stimulate cyanobacteria to secrete more EPS for protection. The extracellular proteins were more sensitive to metal ions, but the interaction between heavy metal ions and polysaccharides was prior to that of proteins. EPS played a significant role in retaining heavy metal ions through surface adsorption.